Safety insights from forensics evaluations at Daiichi. (January 2017) - Rempe, J.; Corradini, M.; Farmer, M.; Gabor, J.; Gauntt, R.; Hara, T.; Luangdilok, W.; Lutz, R.; Luxat, D.; Mizokami, S.; Plys, M.; Robb, K.; et al.
Highlights: Examinations by the Tokyo Electric Power Company at the Fukushima Daiichi Nuclear Power Station to inform Decontamination and Decommissioning activities improves their ability to characterize potential hazards and to ensure the safety of workers involved with cleanup activities. The US Forensics Effort, which is sponsored by the Reactor Safety Technology Pathway of the Department of Energy Office of Nuclear Energy Light Water Reactor Sustainability Program, is using examination information obtained by TEPCO to enhance the safety of existing and future nuclear power plant designs. Examples provided in this paper illustrate that the US Forensics Effort has produced several significant safety insights in the areas of component performance, fission product release and transport, debris end-state location, and combustible gas effects. In addition to reducing uncertainties related to severe accident modeling progression, these safety insights are actively being used by industry to update and improve PWR and BWR guidance for severe accident prevention, mitigation, and emergency planning. Abstract: Although it is clear that the accident signatures from each affected unit at the Fukushima Daiichi Nuclear Power Station [Daiichi] differ, much is not known about the end-state of core materials within these units. Some of this uncertainty can be attributed to a lack of information related to cooling system operation and cooling water injection. There is also uncertainty in our understanding of phenomena affecting: a) in-vessel core damage progression during severe accidents in boiling water reactors (BWRs), and b) accident progression after vessel failure (ex-vessel progression) for BWRs and Pressurized Water Reactors (PWRs). These uncertainties arise due to limited full scale prototypic data. Similar to what occurred after the accident at Three Mile Island Unit 2, these Daiichi units offer the international community a means to reduce such uncertainties by obtaining prototypic data from multiple full-scale BWR severe accidents. Information obtained from Daiichi is required to inform Decontamination and Decommissioning activities, improving the ability of the Tokyo Electric Power Company (TEPCO) to characterize potential hazards and to ensure the safety of workers involved with cleanup activities. This paper reports initial results from the US Forensics Effort to utilize examination information obtained by TEPCO to enhance the safety of existing and future nuclear power plant designs. In this paper, three examples are presented in which examination information, such as visual images, dose surveys, sample evaluations, and muon tomography examinations, along with data from plant instrumentation, are used to obtain significant safety insights in the areas of component performance, fission product release and transport, debris end-state location, and combustible gas generation and transport. In addition to reducing uncertainties related to severe accident modeling progression, these insights confirm actions, such as the importance of water addition and containment venting, that are emphasized in updated guidance for severe accident prevention, mitigation, and emergency planning.